DO MACROECONOMIC VARIABLES HAVE A SYMMETRIC OR ASYMMETRIC EFFECT ON NON-PERFORMING LOANS? EVIDENCE FROM TURKEY - Mehmet Erdaş (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In this study, the existence of therelationships between non-performing loans and macroeconomic variables for themonthly data of the Turkish banking sector between January 2005 and August 2018were analysed through the Johansen cointegration test (1991), VECM Grangercausality test (1988) and Hatemi-J asymmetric causality test (2012). Theresults of the Johansen cointegration test indicated that there are significantcointegration relationships between the variables in long-run. According toGranger causality test based on VECM, unidirectional causalities exists betweennon-performing loans, market capitalisation, exchange rate, industrialproduction index and foreign trade deficit. Except for market capitalization,those causality relationships were determined to be directed from themacroeconomic variables to NPLs. Under Hatemi-J (2012) asymmetric causalitytest, the results revealed that there exists asymmetric causality relationbetween NPLs and other macroeconomic variables excluding the consumer priceindex. It is possible to verify as a result of the analysis that the causalityrelationships between the variables differ and NPLs are affected as long as themacroeconomic conditions change. The results also revealed that the NPLs in theTurkish banking sector are different before and after the recent globalfinancial crisis.